Krishna Basin development: interventions to limit downstream environmental degradation - Venot, Jean-Philippe; Sharma, Bharat R.; Rao, K.V.G.K. (SAGE Publications, 2008)
Since India gained Independence, the Krishna basin has seen an increasing mobilization of its water resources. Warnings of basin closure (minimal flow to the ocean) emerge during dry periods. Basin water development and local rural dynamics have led to a degradation of downstream ecosystems manifesting itself by salinizing soil and groundwater, increasing pollution, making mangroves disappear, and desiccating wetlands. Reversing this evolution requires the formal recognition of the environment as a water user in its own right and the implementation of an environmental water provision. This provision should be based on a two-tier allocation system with assured discharges in the irrigation canals of the delta and to the ocean. This will lead to further commitment of water resources, but this is needed to reconcile the social, economic, and environmental objectives of sustainable development. Other measures facilitating integrated natural resources management from the local to the basin level are needed too.